Morphological and flavonoid pattern variations within some Euphorbia cyparissias L. populations - Papp, Nóra (Acta Biologica Szegediensis, 2005)
The leafy spurge Euphorbia cyparissias L. is a very common and adaptive plant species in Europe. It prefers the xeroterm areas. Eleven populations of this plant were studied in Hungary at different ecological habitats: forest and road edge, swamp field and lime stone rock grass. These areas were exposed to sun to various degree and have different base stones and soil types. Populations have different phenotypes: various stem and cyma height, leaf length and number of branches. We detected two main and other flavonoid components of this plant by TLC and HPLC in different quantity. Altogether 18 flavonoid compounds were detected in the populations by HPLC with very different flavonoid patterns. Plants living at shadowy habitats were higher, they had more leafy branches, leaves and more (9-13) flavonoid constituents. Populations living at sunny areas had smaller stem and leaves, and only 4-9 flavonoid compounds. According to the different morphology and flavonoid pattern the populations were classified into ecotype groups which can be related to the studied ecological habitats. These results prove that Euphorbia cyparissias L. is a very polymorph plant species.